Kajian Etnofarmasi Kelompok Masyarakat Banjar Kepisah Sumerta Kelod Denpasar - Dewi, Ni Luh Kade Arman Anita; Adi Lestari, Ni Putu Wisnu; Suradnyana, I Gede (Usadha, 2023)
Ethnopharmacy is a part of pharmaceutical science that includes understanding medicinal plants used and studying how certain ethnic or community communities use drugs. Studies on ethnopharmaceuticals have never been carried out on the community in the Sumerta Kelod area, especially the Banjar Keseparat community. Where there are still many Banjar Keseparat people who use plants as medicine. This research is a descriptive research. Data collection was done by interview method. The sampling technique in this study used a non-probability sampling method. The results showed that ethnopharmaceutical research that had been carried out in Banjar Kejuangan, Sumerta Kelod obtained in general 12 types of plants that were located in Banjar Kejuangan, Sumerta Kelod. Where the plant parts used were 67% leaves, 17% rhizomes, 8% stems, and 8% flowers. The method of processing plants with the highest frequency was by boiling, which was 92%. The most frequently used method of using ethnopharmaceutical plants is by drinking, which is equal to 83%, and the most frequently used indication for medicinal plants is to treat joint problems, such as muscle pain and gout (28%).